Dysmobility syndrome: Current perspectives - Hill, Keith; Farrier, K.; Russell, M.; Burton, Elissa (Dove Medical Press Ltd., 2017)
Background: A new term, dysmobility syndrome, has recently been described as a new approach to identify older people at risk of poor health outcomes. The aim was to undertake a systematic review of the existing research literature on dysmobility syndrome. Method: All articles reporting dysmobility syndrome were identified in a systematic review of Medline (Proquest), CINAHL, PubMed, PsycInfo, EMBASE, and Scopus databases. Key characteristics of identified studies were extracted and summarized. Results: The systematic review identified five papers (three cross-sectional, one case control, and one longitudinal study). No intervention studies were identified. Prevalence of dysmobility syndrome varied between studies (22%–34% in three of the studies). Dysmobility syndrome was shown to be associated with reduced function, increased falls and fractures, and a longitudinal study showed its significant association with mortality. Conclusion: Early research on dysmobility syndrome indicates that it may be a useful classification approach to identify older people at risk of adverse health outcomes and to target for early interventions. Future research needs to standardize the optimal mix of measures and cut points, and investigate whether balance performance may be a more useful factor than history of falls for dysmobility syndrome. © 2017 Hill et al.